Science as Magic - Gomez-Marin, Alex; Martínez, Luis M; Camí, Jordi (Organisms. Journal of Biological Sciences, 2020)
We draw an analogy between illusionism and scientific research. Based on the conceptual distinction between “external” and “internal life” often used in magic, we discuss how these two worlds also coexist in science, one of them being hardly accessible to both scientists and spectators. The task of the scientist is situated in the context of the spectator of a magic effect, whereas the inner workings of nature are compared to the secret maneuvers of the magician. Such a split and subsequent clash of worlds enables the outcome of the magic trick to produce the so-called “illusion of impossibility”, whose consequences we map to the process of scientific discovery, invention and understanding. We illustrate our proposal with three paradigmatic examples from the scientific and magic literature, and end by discussing the limitations of the analogy and its implications for improving the practice of science. Citation: Gomez-Marin, A, Martínez, LM, Camí, J, 2020, “Science as Magic”, Organisms: Journal of Biological Sciences, vol. 4, no. 1, pp. 90-101. DOI: 10.13133/2532-5876/16756.